2021
DOI: 10.26822/iejee.2021.227
|View full text |Cite
|
Sign up to set email alerts
|

Teachers Experiences on Instructional Design Based Professional Development: A Narrative Inquiry

Abstract: Empowering teachers as instructional designers strengthen the link between theory and good practice. The purpose of the research is to explore two teachers' experiences about a professional development (PD) program. The PD includes a one academic year program with the aim of developing teachers' instructional design knowledge and skills using Understanding by Design model as reference. Teachers' instructional designs improved in terms of UbD design principles, and they reported change in their attitudes and te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Finally, the EFL teachers should employ the existing facilities and infrastructure to support the DC implementation. However, meeting all of the aspects to establish DC in EFL teaching took work (Altun et al, 2022;Endeshaw, 2023;Suprayogi & Valcke, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, the EFL teachers should employ the existing facilities and infrastructure to support the DC implementation. However, meeting all of the aspects to establish DC in EFL teaching took work (Altun et al, 2022;Endeshaw, 2023;Suprayogi & Valcke, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The teachers should map the student's potential by observing one-by-one performance. Moreover, the teachers found finding resources or teaching materials that suit each student's needs and interests difficult since the institution or schools have not fully supported them (Altun et al, 2022). The teachers, again, should spend more time to seek for the material at any time and place and employ their own internet access.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent educational research conducted by Hallinger et al (2018) and Murphy et al (2013) found that teacher evaluation is crucial in improving efficiency and building a functional school management system. Also, the feedback that principals provide in building the capacity and skills of teachers for classroom management has been defined by many researchers as one of the essential elements of successful school leadership (DiPaola & Hoy, 2018), these findings are supported by the research of Altun et al (2021), were teachers insist on receiving detailed feedback regarding their work, with suggestions in each stage regarding teaching process, what they did wrong and how to improve those mistakes. Consequently, by improving the work process in the school, the opportunities for professional development of teachers and improvement of achievement increase for students.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It includes the ability to think critically and solve problems, as well as the ability to understand and use information [3]. Literacy is the ability to identify, understand, interpret, create, communicate, and write about a variety of topics [4,5]. In addition, literacy is the ability to analyze a reading and understand the concepts behind the reading.…”
Section: Introductionmentioning
confidence: 99%